In-vivo anthelmintic activity assessment to dietary incorporation of natural feed additives in sheep: A comparative study - BEIGH, YASIR AFZAL; GANAI, ABDUL MAJEED; WANI, ZAHOOR AHMAD; HAQ, ZULFAQARUL; MIR, SHAHID HASSAN (The Indian Journal of Animal Sciences, 2021)
Anthelmintic activity to dietary incorporation of exogenous fibrolytic enzymes (EFE) and wormwood (Artemisia absinthium L.) herb as feed additives was evaluated. Twenty crossbred lambs (11.58±0.01 kg body weight) were distributed into four dietary treatments in completely randomized design and fed for a period of 90 days followed by 6 day digestibility trial. Animals in all the groups were offered oats straw based total mixed ration added with EFE’s cocktail at 0.60% substrate dry matter (DM) level (T1) or wormwood herb at 4.50% substrate DM level (T2) either alone, and in-combination of the two feed additives (T3), whereas the TMR without addition of any additive served as control (T0). In vivo anthelmintic assays and selected haemato-biochemical parameters of animals were evaluated at start (0d) and subsequently at monthly intervals (30, 60 and 90d). The feed additives in-combination improved nutrient digestibility and digestible nutrient intakes per day. Wormwood herb inclusion had significant positive effect on overall treatment means as well as at each feeding period of per cent faecal egg count reduction and at 90 day period of faecal parasitic eggs per gram assay. Blood profile revealed better physiological health status of lambs fed feed additives compared to those of control group. It is concluded that incorporation of wormwood had better anthelmintic activity and the two feed additives act synergistically in sheep to improve nutrient utilisation and gastrointestinal infested host’s health.